Case report: A case of high grade serous carcinoma of peritoneal origin - Liu, Yiming; Wang, Sixian; Wu, Yingchao; Chen, Guowei; Zhang, Junling; Wang, Xin (Frontiers in Oncology, 2024)
This case report describes an 80-year-old female patient admitted to the emergency department due to abdominal distension, abdominal pain, and hematemesis persisting for three days. Subsequent postoperative pathological examination confirmed the diagnosis of peritoneal cancer. The occurrence, diagnosis, treatment, and prognosis of primary peritoneal cancer (PPC) are presented in detail. PPC is a type of cancer originating from the primary peritoneal mesothelium organization, causing diffuse malignant tumors in the abdominal and pelvic regions. Due to the lack